2020
DOI: 10.3389/fnhum.2020.00063
|View full text |Cite|
|
Sign up to set email alerts
|

Interhemispheric and Intrahemispheric Connectivity From the Left Pars Opercularis Within the Language Network Is Modulated by Transcranial Stimulation in Healthy Subjects

Abstract: Neural activity related to language can be modulated within widespread networks following learning or in response to disruption-including the experimental application of noninvasive brain stimulation. However, the spatiotemporal characteristics of such modulation remain insufficiently explored. The present study combined transcranial magnetic stimulation (TMS) and electroencephalography (EEG) to explore the modulation of activity across the language network following continuous theta-burst stimulation (cTBS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition to traditional speech and language therapy (SLT), repetitive transcranial magnetic stimulation (rTMS), one of the most promising noninvasive brain stimulation (NIBS) modalities, has emerged as an ideal method to improve the language function of patients with PSA ( Ren et al, 2014 ; Kapoor, 2017 ; Gholami et al, 2022 ). rTMS can modulate the excitability and activity of targeted cortical regions, thereby promoting the reorganization of functional networks ( Kapoor, 2017 ; Yoo et al, 2020 ; Jargow et al, 2021 ). Continuous theta burst stimulation (cTBS) is a novel rTMS method that reduces excitability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to traditional speech and language therapy (SLT), repetitive transcranial magnetic stimulation (rTMS), one of the most promising noninvasive brain stimulation (NIBS) modalities, has emerged as an ideal method to improve the language function of patients with PSA ( Ren et al, 2014 ; Kapoor, 2017 ; Gholami et al, 2022 ). rTMS can modulate the excitability and activity of targeted cortical regions, thereby promoting the reorganization of functional networks ( Kapoor, 2017 ; Yoo et al, 2020 ; Jargow et al, 2021 ). Continuous theta burst stimulation (cTBS) is a novel rTMS method that reduces excitability.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that cTBS over the right pars triangularis of individuals with chronic PSA enhanced word retrieval by facilitating phonological access ( Harvey et al, 2019 ). Yoo et al (2020) delivered neuronavigated cTBS over the left pars opercularis in healthy subjects, resulting in significantly increased phase synchronization of TMS-evoked potentials (TEPs) in language areas between the two hemispheres and within the left hemisphere. These results may have implications for the development of a cTBS protocol to assist language rehabilitation in patients with PSA.…”
Section: Introductionmentioning
confidence: 99%
“…Brain stimulation has been widely applied due to its ability to modulate brain plasticity in neuropsychiatric patients ( Davis and Smith, 2019 ; Kim E. et al, 2020 ; Yoo et al, 2020 ). Typically, brain stimulation methods have been classified as invasive or noninvasive brain stimulation (NIBS).…”
Section: Introductionmentioning
confidence: 99%